AN EMPIRICAL EVALUATION OF TOUR GUIDE AND TOURISM POLICY: THE CASE OF BABYLON IRAQ - Muthana Faaeq Almasooudi; Suraiyati Rahman, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The tour guide service is becoming increasingly important due to the booming tourism industry in Iraq; yet, it has been linked to low service standards, insufficient help, and inadequate training for tour guides. This research aimed to learn how Babylon's decision-makers and tour guides view the city's recent progress in the tourist industry and also to determine the role and responsibility of the decision-makers regarding tour guides in Babylon, the processes of participation, and the implication of challenges for tourism. The case study approach was utilized to analyze the Babylon tourism policy and planning system's major stakeholders' responsibilities, activities, and interactions. The case study began in 2023 when the last Babylon tourist plan was created; we acquired all of the information we needed for the study. The case study method has been generally praised as a powerful tool for understanding tourism policy. The implication of the research contributed to this study's interviews taken in Iraq and Babylon has made it possible for us to highlight the significance of such study in the tourism industry's adoption of sustainable practices and their contribution to the expansion and dissemination of sustainable tourism. According to the study's findings, Babylon's decision-makers and tour guides were well aware of the city's inadequate tourist infrastructure and the industry's struggles to keep up with rising visitor numbers. It will take years to complete the many building projects planned for Babylon.